Pannella & Pallone. TeleRoma56’s Glocal Broadcasting between Politics and Entertainment - Crisanti, Giulia; Garofalo, Damiano (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
The paper examines the history of Italy’s local television through the case study provided by TeleRoma56, namely Rome’s first over-the-air local television. In particular, we explore how, through its dual focus on sport and politics, TeleRoma56 combined its commercial exigencies with the strong political characterization of its television programming, constantly presenting its broadcasting as a public service to the citizens. As a result, TeleRoma56’s historical trajectory defies conventional narratives on Italian commercial broadcasting in the course of the 1980s. Conversely to the tendency to interpret Italian private TV as a de-politicized “dream television,” TeleRoma56 prioritized news and political content over entertainment. At the same time, it provided a laboratory to experiment with sportscasting TV formats that mixed commercial and political exigencies. As such, it offers a simultaneously paradigmatic and exceptional case study to re-think our understanding of the history of Italian private television in the transition from RAI’s public monopoly over TV broadcasting to the liberalization of the Italian television landscape.